Vitis vinifera L. Fruit Diversity to Breed Varieties Anticipating Climate Changes - Bigard, Antoine; Berhe, Dargie T.; Maoddi, Eleonora; Sire, Yannick; Boursiquot, Jean-Michel; Ojeda, Hernan; Péros, Jean-Pierre; Doligez, Agnès; Romieu, Charles; Torregrosa, Laurent (Frontiers in Plant Science, 2018)
The wine industry is facing critical issues due to climate changes since production is established on very tight Genotype x Environment interaction bases. While, some cultivation practices may reduce adverse effects of abiotic stresses on the vines, e.g. the use of irrigation to mitigate drought, the deleterious impacts of warming on fruit development are difficult to manage. Elevated temperature alters grapevine fruit growth and composition, with a critical increase of the sugars/organic acids ratio. Select grapes with improved metabolite balances to offset high temperature effects is a valuable option to sustain viticulture. Unfortunately, the lack of knowledge about the genetic diversity for fruit traits impacted by temperature impairs the design of breeding programs. This study aimed to assess the variation in berry volume, and main sugars and organic acids amounts in genetic resources. Fruit phenotyping focused on two critical stages of development: the end of green lag phase when organic acidity reaches its maximum, and the ripe stage when sugar unloading and water uptake stop. For that purpose, we studied a panel of 33 genotypes, including 12 grapevine varieties and 21 microvine offspring. To determine the date of sampling for each critical stage, fruit texture and growth were carefully monitored. Analyses at both stages revealed large phenotypic variation for malic and tartaric acids, as well as for sugars and berry size. At ripe stage, fruit fresh weight ranged from 1.04 to 5.25 g and sugar concentration from 751 to 1353 mmol.L-1. The content in organic acids varied both in quantity (from 80 to 361 meq.L-1) and in composition, with malic to tartaric acid ratio ranging from 0.13 to 3.62. At the inter-genotypic level, data showed no link between berry growth and osmoticum accumulation per fruit unit, suggesting that berry water uptake is not dependent only on fruit osmotic potential. Diversity among varieties for berry size, sugar accumulation and malic to tartaric acid ratio could be exploited through cross breeding. This provides interesting prospects for improving grapevine to mitigate some adverse effects of climate warming on grapevine fruit volume and quality.